Formation and dynamics of a solar eruptive flux tube - Satoshi Inoue (Nature Portfolio, 2018)
Solar eruptions are large explosions occurring in the solar atmosphere. Here, the authors perform magnetohydrodynamic simulations to unveil the dynamics of a solar eruption, and find that these are dominated by nonlinear processes involving flux tube evolution and reconnection.